2017
DOI: 10.11646/zootaxa.4263.3.4
|View full text |Cite
|
Sign up to set email alerts
|

New records of millipedes and centipedes from Bulgaria, with an annotated checklist of the Bulgarian myriapods

Abstract: The present paper records new and poorly known myriapods (Diplopoda, Chilopoda) collected in Bulgaria in the last 10 years. Four new species are reported as new to the Bulgarian fauna: Lithobius melanops Newport, 1845 (Chilopoda: Lithobiomorpha: Lithodiidae), Polydesmus collaris C.L. Koch, 1847, Polydesmus inconstans Latzel, 1884 and Polydesmus schaessburgensis Verhoeff, 1898 (Diplopoda: Polydesmida: Polydesmidae). Scanning electron micrographs of the gonopods and male leg-pairs 5 and 6 are provided for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 834 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Epigean (as the name implies); found at 1200-1950 m a.s.l. Bachvarova et al (2017) reported it from the yard of a summer house, under plywood, and from leaf litter under scattered Pinus and deciduous trees. Dragan Antić (pers.…”
Section: Habitatmentioning
confidence: 99%
“…Epigean (as the name implies); found at 1200-1950 m a.s.l. Bachvarova et al (2017) reported it from the yard of a summer house, under plywood, and from leaf litter under scattered Pinus and deciduous trees. Dragan Antić (pers.…”
Section: Habitatmentioning
confidence: 99%
“… Bacillidesmus bulgaricus bulgaricus — Strasser 1966a : 341, figs 13–15; Strasser 1973 : 419; Stoev 2004 : 149; Stoev 2007 : 384; Beron 2015 : 80, 410; Bachvarova et al 2017 : 521. …”
Section: Resultsunclassified
“… bulgaricus dentatus . Subsequently, both subspecies were recognized as such by Stoev (2004 , 2007 ), Beron (2015) and Bachvarova et al (2017) . On the other hand, Ceuca (1992) , and Kime and Enghoff (2011) considered dentatus as a separate species, B.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations